Gender Implications on Left Ventricular Diastolic Dysfunction in Non Alcoholic Fatty Liver Disease Patients - Hadi, Abdul; Khan, Jibran Umar Ayub; Badshah, Sayed Hilal; Khalil, Saifullah Khan; Ahmad, Iftikhar; Ahmad, Bilal (Journal of Postgraduate Medical Institute, 2025)
Objective: To assess the impact of gender on the risk of Left Ventricular Diastolic Dysfunction in Non Alcoholic Fatty Liver Disease. Methodology: This comparative cross sectional study was conducted at the major hospitals of Khyber Pakhtunkhwa, after proper ethical approval was taken. The sample size was 192, using the non probability purposive sampling. All patients having non alcoholic fatty liver disease on imaging studies were screened for Left Ventricular Diastolic Dysfunction (LVDD) and then were included in the study. Patient with deranged liver function tests and having liver cirrhosis were excluded. The data analysis was conducted using SPSS 23 software package. Results: The mean BMI of the patients was 20. The males comprised 53%(n-102) of the total patients while females accounted for 47% (n-90). The p value of 0.043 does show statistically significant difference in ventricular diastolic dysfunction between both the genders, especially more in female gender. Conclusion: Left ventricular diastolic dysfunction is a common finding in Non Alcoholic Fatty Liver Disease patients having low BMI and female gender. Routine echocardiography should be performed to start the management on time.